tech Function of Input and Output Technology in Computer Hardware and Software Development - Oki Dewa Kevin Fadli Dewa (Journal Basic Science and Technology, 2024)
Data processing in a computer system involves a series of important steps carried out by the processor. Data from input devices, such as keyboards or sensors, is received and converted into a format that the digital system can understand. Via the data bus and address bus, data is forwarded to the processor for processing. The processor retrieves instructions from memory, translates them, and executes those instructions. The results are stored back in memory or sent via the data bus to the output device. This data is then routed through the output controller and, if necessary, converted to a format appropriate to the output device. During the output process, data is conveyed to an output device such as a monitor screen or printer, followed by the execution of appropriate actions. This entire process occurs in a matter of time quickly and repeatedly according to the program instructions executed by the computer. A deep understanding of the relationship between input, processing and output is the key to optimizing computer system performance. The processor, as the processing center, plays a crucial role in bridging the connection between hardware and software to create an effective and efficient computing experience.